Critical Perspective on ASEAN's Security Policy Under ASEAN Political and Security Community - Irawan Jati (Dauliyah Journal of Islamic and International Affairs, 2016)
Despite economic integration challenges, ASEAN faces greater security challenges. It is obvious to assert that a stable economic development requires a secure regional atmosphere. The most probable threats against ASEAN are ranging from hostile foreign entities infiltration, intra and inter states disputes, radical religious movements, human trafficking, drugs and narcotics smuggling, cybercrimes and environmental disasters. In 2009, ASEAN established the ASEAN Political and Security Community as the umbrella of ASEAN’s political and security initiatives. APSC slots in some significant fora; ASEAN Intergovernmental Commission on Human Rights (AICHR), ASEAN Foreign Ministers Meeting (AMM),  ASEAN Regional Forum (ARF), ASEAN Defense Minister’s Meeting (ADMM), ASEAN Law Ministers Meeting (ALAWMM), and ASEAN Ministerial Meeting on Transnational Crimes (AMMTC). The wide array of these forums signify ASEAN efforts to confront double features of security; the traditional and nontraditional or critical security. The traditional security considers state security as the primary object security. While the critical security tends to focus on non-state aspects such as individual human being as its referent object. Even though some argue that APSC has been able to preserve the stability in the region, it still lack of confidence in solving critical issues such as territorial disputes and irregular migrants problems.Therefore, this piece would examine the fundamental questions: How does ASEAN address beyond state security issues in its security policy through APSC? To search for the answer this paper would apply critical security studies approach. Critical security posits that threats are not always for the states but in many cases for the people. Based on the examination of ASEAN security policies, this paper argues that ASEAN’s security policy has touched the non-traditional security issues but showing slow progress on its development and application.